Rigid‐Flexible Coupling Realized by Synergistic Engineering of the Graphitic‐Amorphous Architecture for Durable and Fast Potassium Storage - Mingchi Jiang; Ning Sun; Bin Cao; Xuyang Jian; Razium Ali Soomro; Bin Xu (Advanced Science)
Abstract Graphite anodes hold great potential for potassium‐ion batteries (PIBs), yet their practical application is hindered by poor cycle performance caused by substantial interlayer expansion. Herein, a partial graphitic carbon (PGC) is elaborately engineered via the catalytic effect of ferric citrate using pitch as a carbon precursor. Systematically varying the catalyst content enables an optimal PGC design integrating a highly graphitized phase providing abundant active sites for K‐ion intercalation, balanced with an amorphous carbon region that accommodates volume expansion and facilitates ion diffusion. The optimized PGC12 electrode exhibits a high reversible capacity of 281.9 mAh g−1, characterized by a prolonged low‐potential plateau region, and excellent cycle stability with a capacity retention of 94.8% after 300 cycles. It also realizes an impressive rate capability with a retained capacity of 222.2 mAh g−1 at 1 C. Moreover, the assembled K‐ion full‐cell delivers an exceptional energy density of 148.2 Wh kg−1. In‐situ XRD and DFT simulations further verify the distinct phase transition mechanisms and reaction dynamics across different carbon configurations. This work elucidates the impact of carbon configurations on K‐storage performance and proposes a structural model for efficient K‐ion storage, which is instrumental in the rational design and advancement of carbon anodes in PIBs.